(3JOQjS GdJGQjN Hjf GdEHSJehdhLjG hGdEjOhdhLjGs - (3YHO GdeSjM, Sjehfs ((3HjQhJs (3efThQGJ GdeQcR GdEbdjej ddJhKjb hGdOQGSGJ GdJGQjNjI hGdSjGSjI hGdJQHhjIs, 2012)
(3YbOGf ef GdRef, h(B"(3GdWHNI HMU(B" (3efgL GdJGQjN aj dHfGf, de JfVL HYO(B. (3EfgG hGMOI ef CReGJ GdfXGe GdSjGSj GdLOjO EKQ GdJYOjdGJ GdOSJhQjI YGe (B1990(3, dG Hd jfOQL GdeCRb aj SjGb SeGJ (B"(3GdeQMdI GdGfJbGdjI(B". (3agd GROGO hYj GdWhGFa HhLhOgG GdJGQjNj, hHhRfgG GdSjGSj OGNd GdfXGe, hJQjO dgPG GdhYj hGdhRf Cf jJLSOG aj efgL GdJGQjN GdhWfj hJaSjQGJg? hdeGPG de JfLM HYO eMGhdI JYOjd GdEjOhdhLjI GdQSejI dJchf CcKQ JeKjdG ceG MOK aj GdejOGf GdSjGSj? Ke Edi Cj MO jJWGHb Ch jJfGbV GdhYj GdEHSJhdhLj YfO GdLeGYI GdJGQjNjI GdYdejI, eY GdEjOhdhLjG GdQSejI h(B"(3NUhUjJgG(B" (3GddHfGfjI, hcja Je GdJhajb HjfgeG? HGdEVGaI Edi gPg GdETcGdjI GdeQcRjI, jYGdL GdcJGH bVGjG CNQi JJYdb HJMdjd efgLj GdJGQjN GdUGOQjf aj GdYbO GdChd ef gPG GdbQf, hHNGUI (B"(3GdJhGab(B" (3Hjf HfjI GdZGjGJ hGdCgOGa, h(B"(3GdeOi(B" (3GdRefj GdecGfj hGdehVhYGJj, heTcdGJ (B"(3GdJOQL(B"(3, hGdUdGMjI hGdedGAeI(B.. (3ceG jYGdL GdJWhQ GdPj MOK Hjf GdefgLjf aj GdejOGfjf GdCHSJehdhLj hGdWQGFaj(B-(3GdejJhOhdhLj(B.s
(3GdfhY (B: (3cJGHs
Keywords: curricula; textbooks; (3GdcJH GdeOQSjIs; (3GdefGgLs; Enseignement de l'histoire, manuels scolaires, curricula; Teaching history; (3JYdje GdJGQjNs